АВТОМАТИЧЕСКОЕ ПОСТРОЕНИЕ ПРИ ЦЕНТРАЛЬНОЕ ПРОЕЦИРОВАНИЕ ПРИ ПОМОЩИ AVTOCAD - Буранов, И.Ф.; Аманиязов, С. (SCIENCE and SOCIETY, 2022)
The article discusses one of the methods of central projection of descriptive geometry and its practical application in the scientific and technical aspect.